N07 A qualitative study of the impact of inflammatory bowel disease on partners. (27th May 2021) - Thapwong, P; Norton, C; Terry, H; Czuber-Dochan, W
Abstract: Background: Inflammatory Bowel Disease (IBD) not only impacts the quality of life of the patient, but also affects their family members. Studies to date have provided an understanding of impact of IBD and IBD implications for people with IBD. However, little is known about the impact of IBD on their family members. Therefore, the current study aimed to explore the lived experience of people with IBD and their family members regarding the impacts of IBD on family members and their coping methods. Methods: Twelve participants, including six people with IBD with their six partners, were purposively selected, no other family members (parents / children, sibling) came forward to participate in the study. The in-depth, semi-structured online interviews were conducted via Skype, Zoom, or Microsoft Teams between February-June 2020. Interviews were audio-recorded, transcribed verbatim, and analysed using inductive thematic analysis by Braun and Clarke. Results: Four main themes emerged during the analysis under the central theme "our relationship with IBD, for better or worse". IBD affected the partners in terms of their own relationship, relationship with others, everyday life, and emotional and mental well-being. The theme "our relationship" showed the impact of IBD on the relationship between a couple, including the intimate relationship, family planning, role change as partner and carer, and the importance of honest communication. IBD also affected wider relationships with family, children, and social life, but teamwork could mediate negative impact in relationships. Emotional well-being was impacted by living in constant fear and guilt. Humour and knowledge of IBD reduced negative impacts. IBD impacts on everyday life (diet, finances, and travel) for both patients and partners. Planning for uncertain situations was helpful to reduce restrictions. Conclusion: The study provides an understanding of IBD impact on partners and the coping strategies from patients and partners' perspectives. There are wide-ranging implications for health and social care professionals caring for people with IBD and their families. Social support has been recognised as a vital buffering mechanism in facilitating an individual's adjustment to IBD. Healthcare professionals and researchers may integrate a bio-psycho-social approach into their work with IBD family members. There is a need to develop interventions to help family members of IBD patients to better cope with the illness and to have a more fulfilling life.